Situational Analysis of Human Development in Nepal - Pyakurel, Raja Ram (Sahayaatra सहयात्रा, 2023)
Human Development as progress towards greater human well-being, and provided country-level data for a comparing country status based on the well-being indicators. The main objective of the study is to analyze the overall human development status of Nepal. Data were collected through the national census and survey, UNDP HDI reports and online materials. According to the HDI report 2021\22 Nepal perform in the 143rd position with a 0.602 value. The trend of HDI is increasing despite 2021 \22. Nepal's HDI achieved the highest index in 2019 with 0.611 after 29 years. Nepal uplifted into medium development human development. In SAARC countries Nepal's HDI value is comparatively low compared with Sri Lanka, Bhutan, Maldives and India. Bagmati province ranks at the top and Madesh and Karnali provinces perform worst in HDI, GDI, GII and MPI indices according to the HDI Report 2020. Bagmati and Gandaki provinces have high literacy, life expectancy and GDP per capita. Between 1990 to 2022 Nepal's HDI value changed from 0.399 to 0.602 a change of 50.9%, during the period. For the improvement of the HDI indices, the government should formulate and implement appropriate policies which shape the regional and national targets.